Prospek Pariwisata Kota Ambon dengan Mempertahankan Brand Ambon City of Music - Sinay, Francisca Riconita; Salong, Amjad (Universitas Pattimura, 2024)
Ambon City holds significant potential in the tourism sector through its unique cultural identity in music. However, the utilization of the “Ambon City of Music” brand remains suboptimal due to weak stakeholder synergy and limited supportive infrastructure. This study aims to analyze the tourism development prospects of Ambon by maintaining its music brand as a strategic identity. The research employs an exploratory-qualitative approach using field observations, interviews, and document analysis. Findings reveal that the music brand significantly contributes to building cultural-based tourism appeal, but lacks comprehensive support from regulations, physical infrastructure, and public awareness. Despite UNESCO's recognition of Ambon as a World Music City, there has been no visible transformation of the city’s spatial identity. The study highlights the importance of integrating cultural promotion with urban infrastructure enhancement to achieve global positioning. Recommendations include optimizing music-playing regulations, establishing musical landmarks, and promoting music education across sectors. This research contributes to developing a sustainable, identity-based tourism management model.